Exploring the practice of nutritional support during hospitalization across physicians, dietitians, and pharmacists based in Saudi Arabia - Ajabnoor, Sarah M.; Zaher, Sara; Malatani, Rania; Jawa, Hani (Frontiers in Nutrition, 2023)
Background: Nutritional support has a pivotal role in preventing and treating malnutrition. Recognizing the gaps in nutritional support practice can aid the development of tailored nutritional protocols. Therefore, this study aimed to assess the current practices, attitudes, and perceptions related to nutritional support for hospitalized patients in one of the largest Middle Eastern countries. Methods: A cross-sectional study was conducted among different healthcare professionals currently working in hospitals in Saudi Arabia and involved in nutritional support practice. Data were collected using convenient sample via a self-administered web-based questionnaire. Results: A total of 114 participants were included in this study. The majority were dietitians (54%), followed by physicians (33%) and pharmacists (12%), and were from the western region (71.9%). Various attitudes in many practices were observed among the participants. Only 44.7% of the participants had a formal nutritional support team. The mean confidence level of all respondents was significantly higher for enteral nutrition practice (7.7 ± 2.3) than for parenteral nutrition practice (6.1 ± 2.5) (p < 0.01). The confidence level for enteral nutrition practice was significantly influenced by nutritional qualification (β = 0.202, p < 0.05), type of healthcare facility (β = 0.210, p < 0.05), profession (β = −0.308, p < 0.01), and years of experience (β = 0.220, p < 0.05). Conclusion: This study comprehensively assessed various aspects of nutritional support practice in Saudi Arabia. Healthcare practice of nutritional support should be guided by evidence-based guidelines. Professional qualification and training in nutritional support are essential for promoting practice in hospitals.